2006
DOI: 10.1517/14656566.7.15.2139
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin for the treatment of generalised anxiety disorder

Abstract: Pregabalin is a new anxiolytic that has been recently licensed for the treatment of generalised anxiety disorder (GAD) in Europe. Short-term efficacy is based on six positive placebo-controlled studies, all of which showed a significant early separation from placebo in all of the doses used (150-600 mg) at the first week, and the efficacy at the end of the treatment was comparable with the comparators used in four of these studies. Pregabalin was effective in more or less severe GAD, on psychic and somatic sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 56 publications
(43 reference statements)
3
31
0
1
Order By: Relevance
“…venlafaxine, O-desmethyl-venlafaxine, duloxetine, milnacipran, buspirone, hydroxyzine, and benzodiazepines, low-dose anti-psychotics, and pregabalin (Ballenger, 1991;Montgomery, 2006). Nevertheless, all pharmacological treatments for GAD can cause troublesome side effects, including nausea, sexual dysfunction, and weight gain for the antidepressants (Kennedy et al, 1999(Kennedy et al, , 2001, and anterograde memory impairment, sedation and the risk of dependence with benzodiazepines; therefore, they are not recommended for long-term use (Michelini et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…venlafaxine, O-desmethyl-venlafaxine, duloxetine, milnacipran, buspirone, hydroxyzine, and benzodiazepines, low-dose anti-psychotics, and pregabalin (Ballenger, 1991;Montgomery, 2006). Nevertheless, all pharmacological treatments for GAD can cause troublesome side effects, including nausea, sexual dysfunction, and weight gain for the antidepressants (Kennedy et al, 1999(Kennedy et al, , 2001, and anterograde memory impairment, sedation and the risk of dependence with benzodiazepines; therefore, they are not recommended for long-term use (Michelini et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Current pharmacological treatment options for GAD include antidepressants, such as selective serotonin reuptake inhibitors (SSRIs) and the serotonin-norepinephrine reuptake inhibitor (SNRI), venlafaxine, buspirone, hydroxyzine, benzodiazepines (Ballenger et al, 2001) and pregabalin (Montgomery, 2006). However, the response to these treatments is highly variable, ranging from 40% to 70% (Baldwin & Nair, 2005;Gelenberg et al, 2000;Pollack et al, 2001;Rickels, Downing, Schweizer, & Hassman, 1993).…”
mentioning
confidence: 99%
“…1 PGB is a new anxiolytic that has been licensed for the treatment of (i) GAD, (ii) central and peripheral neuropathic pain (iii) neuropathic pain associated with diabetic peripheral neuropathy and PHN, (iv) partial onset seizures in (v) treating psychic and somatic symptoms of GAD and (vi) in subsyndromal depressive symptoms of GAD in Europe. 21 Studies have demonstrated that premedication with PGB is effective for the prevention of post-operative pain in patients after coronary artery bypass grafting.…”
Section: Role In Therapymentioning
confidence: 99%